2021
DOI: 10.18502/tkj.v12i4.5877
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between workplace ergonomics and musculoskeletal pain, range of motion and spinal deformities in employees: A case study, Kermanshah Oil Refinery

Abstract: Introduction: Today, the health of human resources in organizations is considered an important arm. This study aimed to investigate the relationship between workplace ergonomics and musculoskeletal pain, joint range of motion (ROM), and spinal deformities in Kermanshah oil refinery staff. Materials and Methods: In the present descriptive-analytical study, all official employees of Kermanshah Oil Refinery (n = 300) were invited to participate in the study, in which 160 employees participated as a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ergonomic hazards in the workplace are systematically identified to design preventive and control measures to reduce risk factors which are usually associated with the development of musculoskeletal disorders (MSD). As observed in the case study conducted by Gandomi et al (2021) in Kermanshah Oil Refinery, they have found out that chronic musculoskeletal pain, hyperkyphosis and hyperlordosis, and abnormal joint range of motion experienced by the staffs are all strongly correlated with poor workplace ergonomics. Aside from affecting worker's health, poor workplace design also appears to have direct influence on how productive the workers would be.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Ergonomic hazards in the workplace are systematically identified to design preventive and control measures to reduce risk factors which are usually associated with the development of musculoskeletal disorders (MSD). As observed in the case study conducted by Gandomi et al (2021) in Kermanshah Oil Refinery, they have found out that chronic musculoskeletal pain, hyperkyphosis and hyperlordosis, and abnormal joint range of motion experienced by the staffs are all strongly correlated with poor workplace ergonomics. Aside from affecting worker's health, poor workplace design also appears to have direct influence on how productive the workers would be.…”
Section: Literature Reviewmentioning
confidence: 90%